Agency theory approach of the relationship between performance, compensation and value creation in the companies listed on Euronext Lisbon - Serapicos, Armando (2020)
The aim of the present study was to understand, in Portugal, relationships between the Chief Executive Officer (CEO) and the organizational performance, on the one hand, and relationships between the shareholder value creation and the CEO total compensation, on the other hand. This research is divided into two parts. The first part was examined whether organizational performance based on accounting measures influences organizational performance based on market measures and whether organizational performance based on accounting measures and market measures influences the CEO total compensation. The second part of the study analyses whether organizational performance, based on accounting measures and market measures, and the CEO total compensation influence the shareholder value creation. This research was based on agency theory assumptions in order to build the analysis model. The sample was composed of companies listed on Euronext Lisbon. The data analysis was performed using the structural equation modelling method. The results showed that organizational performance based on accounting measures influences organizational performance based on market measures, the CEO total compensation and the shareholder value creation.